THE INFLUENCE OF TRUST AND MISTRUST ON INTERNATIONAL RELATIONS - Oleksii Batalov (Вісник Харківського національного університету імені В. Н. Каразіна: Серія "Питання політології", 2021)
The influence of trust and mistrust on international relations is considered. The difference between such phenomena as «culture of trust», «culture of mistrust» and «culture of disbelief» is shown. Based on actual examples, it is analyzed how trust-based international relations are formed (special attention is given to whether the states follow written and unwritten “rules of the game”), how trust can be broken down and mistrust can grow, and how trust can be restored in international relations (two ways to restore trust are provided: gradual mutual tension reduction and valuable signals).